Multifunctional Au@mSiO2/Rhodamine B Isothiocyanate Nanocomposites: Cell Imaging, Photocontrolled Drug Release, and Photothermal Therapy for Cancer Cells. Issue 4 (30th October 2012) - Jiang, Zhenlong; Dong, Biao; Chen, Boting; Wang, Jing; Xu, Lin; Zhang, Shuang; Song, Hongwei
Abstract: The synthesis of Au@mesoporous SiO2 /rhodamine B isothiocyanate (Au@mSiO2 /RBITC) composite nanoparticles (NPs) is presented and their unique biofunctional properties are studied. The structure and morphology of the NPs are characterized by X‐ray powder diffraction, transmission electron microscopy, and Fourier transform infrared spectroscopy. These NPs can not only be functionalized for fluorescence imaging, but also possess well‐defined mesopore structures for drug loading and strong infrared surface plasmon absorption for light‐controlled drug release and photothermal therapy for cancer cells. In the biological experiments, one 808 nm laser is coupled to a confocal laser scanning microscopy (CLSM) system to monitor the photothermal therapy, drug release, and cell position and viability in real time by using the multichannel function of CLSM for the first time. Such novel nanomaterials offer a new chemotherapeutic route for cancer treatment by combining cell imaging and hyperthermia in a synergistic way. Abstract : Multifunctional Au nanorod@mesoporous SiO2 /rhodamine B isothiocyanate (RBITC) composite nanoparticles have been prepared, which possess the functions of bright photoluminescence for bioimaging, well‐defined mesopore structures for drug loading, and strong infrared surface plasmon absorption for light‐controlled drug release and photothermal therapy for cancer cells. Photothermal therapy, drug release, and cell viability are monitored in real time through the multichannel function of laser confocal scanning microscopy.